EFEKTIVITAS PELAKSANAAN PERATURAN DAERAH NOMOR 14 TAHUN 2012 TENTANG RETRIBUSI IZIN TRAYEK DI KOTA PEKANBARU TAHUN 2013 - Suwandi, Evita; Indra, Mexsasai; Ghafur, Abdul (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2014)
Effectiveness of the implementation of the Regional Regulation No. 14 Year 2012 on Route Permits in Pekanbaru city in 2013 had not been effective. It can be seen from some licensing issues that do not stretch done / taken care of by the owners of the transport business in the city of Pekanbaru. The purpose of this thesis to determine, first, the effectiveness of the implementation of the Regional Regulation No. 14 Year 2012 on Route Permits in Pekanbaru city in 2013 Secondly, the obstacles encountered in the implementation of the Regional Regulation No. 14 Year 2012 on Route Permits in Pekanbaru city in 2013. third, the efforts of the Department of Transportation, the city of Pekanbaru to overcome obstacles in the implementation of the Regional Regulation No. 14 year 2012 on Route Permits in Pekanbaru city in 2013.Effectiveness - Implementation - Regional Regulation